2016
DOI: 10.1097/jnr.0000000000000098
|View full text |Cite
|
Sign up to set email alerts
|

A Quality of Working Life Survey Instrument for Hospital Nurses

Abstract: The information obtained using the questionnaire may improve workplace audit outcomes, promote occupational health, and improve service quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Previous research has established that the work engagement in healthcare is problematic [5]. Simpson did a systematic literature review related to work engagement in the context of nursing and found 32 papers on the topic, most of which focused on the antecedents and/or consequences of engagement at work [26].…”
Section: Work Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has established that the work engagement in healthcare is problematic [5]. Simpson did a systematic literature review related to work engagement in the context of nursing and found 32 papers on the topic, most of which focused on the antecedents and/or consequences of engagement at work [26].…”
Section: Work Engagementmentioning
confidence: 99%
“…However, recent reports by Golay suggests unexpected work and invisible new tasks are being introduced as a result of new technology [4]. Given the work environment problems in healthcare, with a large turnover of especially nurses [5] and recent evidence that suggest digitalisation is experienced as a part of the problem by many healthcare professionals [6,7], it is vital to investigate the effects of automation and digitalisation on work engagement.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that working life is an important and meaningful part of personal life so that Hsu citing Frell considered occupation as one of the factors affecting the quality of life[16] because occupational stress is recognized as a very important factor affecting a person's quality of life. [17] Meanwhile, hospitals, as organizations, can seriously exert pressure on clients and especially nurses, which will subsequently have their own physical and psychological effects because nursing profession is inherently stressful and stress can similarly affect the nurses' quality of life and health status.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has established that the work environment for nurses in health care is problematic (Hsu, 2016). Alarming research shows that among young nurses, every fifth nurse strongly intended to leave the profession five years after graduation, and the intention was associated with levels of burnout (Rudman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%